The role of RNA structure in regulating pre-mRNA splicing - Warf, M. Bryan (2009)
Pre-mRNA splicing is the process of removing non-coding introns from RNA transcripts and is carried out by the spliceosome, along with other auxiliary factors. In general, research in splicing has focused on the sequences within the pre-mRNA, without taking into account the structures that these sequences might form. However, we propose that the role of RNA structure deserves more consideration when thinking about splicing mechanisms. RNA structures can inhibit or aid binding of spliceosomal components to the pre-mRNA, or can increase splicing efficiency by bringing important sequences into close proximity. Recent reports have also identified proteins and small molecules that can regulate splicing by modulating RNA structures, thus expanding our knowledge of the mechanisms used to regulate splicing.